Overexpression of hypoxia-inducible factor 1α and excessive vascularization in the peri-implantation endometrium of infertile women with chronic endometritis - Liu, Zhenteng; Liu, Xuemei; Li, Fenghua; Sun, Yuxia; Yu, Lili; Zhang, Wei; Zhu, Ping; Ma, Ding; Wang, Xinrong; Lai, Shoucui; Bao, Hongchu (Frontiers in Endocrinology, 2022)
Objective: Chronic endometritis (CE) contributes to impaired endometrial receptivity and is closely associated with poor in vitro fertilization (IVF) outcomes. However, the mechanisms underlying CE are unclear. Here, we investigated the role of the hypoxic microenvironment and endometrial vascularization in the peri-implantation endometrium of infertile women with CE. Methods: This retrospective study involved 15 fertile women and 77 infertile patients diagnosed with CE based on CD138+ ≥1/10 HPFs. The CE patients were divided into Group 1 (CD138+ 1–4/10 HPFs, 53 cases) and Group 2 (CD138+ ≥5/10 HPFs, 24 cases). The expression levels of hypoxia-inducible factor 1α (HIF1α), vascular endothelial growth factor A (VEGFA), and vascular endothelial growth factor receptor 2 (VEGFR2) in peri-implantation endometrium were assessed by qRT-PCR and western blot analyses. Spatial levels of HIF1α, VEGFA, and VEGFR2 in various endometrial compartments was determined using immunohistochemistry and H-score analysis. Microvascular density (MVD) was determined using CD34 staining and scored using Image J. Finally, we used qRT-PCR to assess changes in the expression of HIF1α, VEGFA, and VEGFR2 in CE patients after treatment with first-line antibiotics. Result(s): Relative to Group 1 and control group, during the implantation window, protein and mRNA levels of HIF1α, VEGFA, and VEGFR2 were markedly high in Group 2 (P<0.05). H-score analysis showed that HIF1α, VEGFA, and VEGFR2 in the luminal, glandular epithelium, and stromal compartments were markedly elevated in Group 2, comparing to control group and Group 1 (P<0.05). Moreover, markedly elevated MVD levels were observed in Group 2. Notably, the above indexes did not differ significantly in the control group versus Group 1. Treatment with antibiotics significantly suppressed the endometrial HIF1α and VEGFA levels in CE-cured patients. Conclusion(s): Here, we for the first time report the upregulation of HIF1α, VEGFA, and VEGFR2, as well as excessive endometrial vascularization in the peri-implantation endometrium of CE patients. Our findings offer new insights into reduced endometrial receptivity in CE-associated infertility.